IMPLEMENTING RECIRCULATION SYSTEMS IN UKRAINIAN AQUACULTURE: INTERSECTORAL ECONOMIC MEASURES AND PROPOSALS - Tiutiunnyk, Hanna; Iermakova, Olga (Collection of scientific papers «ΛΌГOΣ», 2023)
Water recirculation systems in aquaculture, also known as RAS (Recirculating Aquaculture Systems), represent a new alternative to traditional fish farming methods with several important advantages. These human-controlled systems provide efficient water conservation, fish health preservation, and increased productivity.